Museum-worthy smartwatches: A medical humanities perspective - Riet, Gontse (School of African and GenderStuds, Anth and Ling, 2025)
This thesis focuses on the relationships that bind people to their smartwatches along the Sea Point Promenade in the city of Cape Town. The study identifies smartwatches as objects with immense social, personal, and interpersonal traction. Materiality in anthropology is well explored and offers a range of theoretical tools for bridging the gap between human and machine as well as functional design and aesthetic. Research with ordinary smartwatch users invites inquiry into aspects of their use that directly affect health, well-being, illness detection and monitoring. Smartwatches are also branded and displayed in ways that signify class and aspirations. These aspirations are coded by their functional, symbolic, and artistic value. The research draws upon a comprehensive body of literature to contextualize and analyse how individuals utilize and perceive these devices, offering revitalized perspectives on smartwatches as machines that gesture towards ideas of convivial social relations. Conviviality puts the immediate in the larger context and the larger context in the immediate through deliberate connections, but also acknowledging the hierarchies and conflicting interests at play at the small and large scales of existence and consciousness. With a multimodal anthropological approach, the dissertation includes stories gathered over six months through ethnographic methods including participant observation, interviews, and the examination of public documents and artifacts. The research also explores audio reporting as a valuable tool for anthropology and ethnographic storytelling, providing insights into how people use, perceive, and experience smartwatches. The intriguing relationship between smartwatches and people's lived experiences in modern urban environments is explored as a way to contribute to the expanding conversation on the interplay between technology, health, and society. It emphasises the intricate relationship that shapes the contemporary healthcare landscape between technology innovation, societal norms, and individual autonomy through nuanced storytelling and critical analysis.